MODERN APPROACH TOWARDS IMMUNOMODULATION THERAPY - L. S. Namazova-Baranova; E. A. Vishneva ("Paediatrician" Publishers LLC, 2012)
This article covers one of the most discussed issues of clinical immunology - the role of dendritic cells in acquired immunity. Modern conception of dendritic cells participating in antigen handling procedure and its presentation, interaction with other immune cells made it possible to change approach towards immunomodulating therapy dramatically and to develop a new class of immunostimulants, that influence simultaneously cell and humoral immunity both in loci of antigen intervention on the mucosal level and systemically.